2021
DOI: 10.1007/s10643-021-01240-y
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Primary School of Children in Economic Disadvantage: Does a Preschool Teacher Training Program Make a Difference?

Abstract: Transition to school may be experienced as a critical event for both children and their families. Within an ecological framework of transition, the scope of the concept of school readiness in recent years has decentered from the child to the environment, including the readiness of (pre)school education to develop core skills in children. This study aims to understand the extent to which a preschool teachers completion of training in the Incredible Years® -Teacher Classroom Management program (IY-TCM) during ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Children with disadvantages may have a lack of appropriate social skills for different reasons, such as insufficient experience with their peers (Frostad & Pijl, 2006). Therefore, interventions that address all these factors holistically are needed, and it is thought that it will help reduce the inequality of opportunity created by disadvantages (Seabra-Santos et al, 2021).…”
Section: Problems Experienced In the Transitionmentioning
confidence: 99%
“…Children with disadvantages may have a lack of appropriate social skills for different reasons, such as insufficient experience with their peers (Frostad & Pijl, 2006). Therefore, interventions that address all these factors holistically are needed, and it is thought that it will help reduce the inequality of opportunity created by disadvantages (Seabra-Santos et al, 2021).…”
Section: Problems Experienced In the Transitionmentioning
confidence: 99%
“…Research shows that disadvantaged groups usually have inadequate creativity development. For example, people who grew up in disadvantaged families tended to have less stimulating home environments, insufficient parental involvement, and experienced maladaptation at school, resulting in inadequate personal development ( Rothe et al 2014 ; Seabra-Santos et al 2021 ; Skopek et al 2017 ). Due to inadequate development, the creative performance of people in disadvantaged situations cannot be compared with people in advantageous situations ( Xu and Pang 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that one effective protective factor of inadequate development is the teacher’s positive behavior (e.g., specific praise and encouragement). Specifically, Seabra-Santos et al ( 2021 ) found that teachers give more specific praises when they follow a training program that both promotes the students’ development and reduces the effect of student’s socio-economic disparity. Similarly, van der Zanden et al ( 2020 ) summarized that encouraging adolescents to express their ideas is beneficial to their creativity development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El contexto actual, caracterizado por la alta demanda de la tecnología para la enseñanza a raíz de las condiciones sanitarias producidas por la pandemia del COVID-19 afectando la educación presencial a nivel mundial, ha evidenciado la escasa preparación de las profesionales en cuanto a cómo utilizar los recursos tecnológicos para la promoción de los aprendizajes (Avendaño et al, 2021). La educación parvularia, como primer nivel educativo es responsable de insertar al niño en la educación formal, brindándoles las herramientas necesarias que le permitan responder de mejor manera a las necesidades que se le presentan en su entorno, como plantean Kokanović (2019) y Seabra-Santos et al, (2021), es la educación inicial la encargada de aportar al estudiante elementos que le permitan desarrollar habilidades como la autonomía, la resolución de problemas simples que faciliten su integración al medio social. Para los autores es esencial contar con profesionales que cuenten con los conocimientos necesarios para contribuir con experiencias pedagógicas lúdicas que motiven a los niños a aprender.…”
Section: Introductionunclassified